Incentivising Safe Sex : A Randomised Trial of Conditional Cash Transfers for HIV and Sexually Transmitted Infection Prevention in Rural Tanzania - de Walque, Damien (BMJ Publishing Group, 2015)
The authors evaluated the use of conditional cash transfers as an HIV and sexually transmitted infection prevention strategy to incentivise safe sex. Conditional cash transfers used to incentivise safer sexual practices are a potentially promising new tool in HIV and sexually transmitted infections prevention.